Development of a framework to evaluate service-oriented architecture governance using COBIT approach - M. Dehghani; S. Emadi (Journal of Artificial Intelligence and Data Mining, 2016)
Nowadays organizations require an effective governance framework for their service-oriented architecture (SOA) in order to enable them to use a framework to evaluate their current state governance and determine the governance requirements, and then to offer a suitable model for their governance. Various frameworks have been developed to evaluate the SOA governance. In this paper, a brief introduction to the internal control framework COBIT is described, and it is used to show how to develop a framework to evaluate the SOA governance within an organization. The SOA and information technology expert surveys are carried out to evaluate the proposed framework. The results of this survey verify the proposed framework.